THE DEVELOPMENT OF TOURISM ROUTES BASED ON COMMUNITY CULTURE IN LOEI PROVINCE - Roonkaseam, Nitta; Jukrkorn, Narongsak; Sompuet, Preeya; Wilailuk, Nisararat; Puengsangwal, Sirimon; Tongchum, Pratchaya; Koograsang, Apisak; Thongdaeng, Hassaporn (Academic Journal Phranakhon Rajabhat University, 2021)
The research on the development of tourism routes based on community culture in Loei Province is aimed to develop tourism routes and activities based on community culture in Loei Province. The qualitative research method includes documentary analysis, focus group discussion, and community forums with the travel agent Na Aor community and Saeng Pha community. The development of tourism routes based on community culture in Loei province can develop in two routes. Which are (1) The way of life along the Mekong River (Na Aor, Lan Xang Cultural Way) featured an old wooden house, Tai Loei architecture, and learning about Tai Lei people's way of life through the wisdom of Ban Na Or architecture. And (2) indigenous culture routes (Faith Way of Saeng Pha) are featured at Wat Pho Chai, a 400-year-old temple and a center of faith in the community. Also, exciting culture and tradition are the flower parade that reflects the dedication and Buddhist teachings.